Bridging the Gap Interfaith Competence as a National Security Strategy in Multireligious Indonesia – Perspectives from Christian Educators - Roce Marsaulina; Gilbert Timothy Majesty (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This qualitative study addresses the critical gap between religious diversity and national security in Indonesia by proposing interfaith competence as a strategic imperative. Situated within a constructivist framework, the research investigates the perspectives of Christian educators, positing that their unique position at the intersection of faith formation and pedagogy offers invaluable insights into building sustainable religious harmony. Constructivism provides the analytical lens, emphasizing that understandings of religious